Maximizing Labor Utilization in Garment Production Line Using the Simulation Technique (Journal of Fiber Bioengineering and Informatics, 2020)
Line balancing problems are common in the various departments of the garment industry. Different kindsof line balancing algorithms have been applied, for many years, in the apparel industry to solve theseproblems. Many variables and constraints must be taken into account when designing a manufacturingfacility, such as the assembly line balance. For this purpose, lots of data have been collected fromactual production systems, as well as alternative ones, in order to find the best line balancing algorithm.Studying the factors affecting line balancing, to identify the bottlenecks and enhance production systemperformance, is of utmost importance.Garment manufacturing firms, particularly those working on a small-lot and order basis, must respondrapidly to changes in clothing styles. For flexibility and fast response, the line manger must be awareof the current situation in his production system, in order to process orders on time. Furthermore, inorder to increase productivity, it is essential for line managers to be able to understand the behaviorof the production system and to generate alternative systems. Thus, the simulation model approach,developed for the garment industries, enables predictability and helps to increase total productivity.The aim of this research is to simulate a production line producing several models at the same time,in order to find the maximum number of products in a product mix that can be manufactured, at highquality and without wasting time. Results show that it is possible to produce up to five different productssimultaneously on the same line.